2014
DOI: 10.5339/qmj.2014.1
|View full text |Cite
|
Sign up to set email alerts
|

Bed crisis and elective surgery late cancellations: An approach using the theory of constraints

Abstract: Late cancellations of scheduled elective surgery limit the ability of the surgical care service to achieve its goals. Attributes of these cancellations differ between hospitals and regions. The rate of late cancellations of elective surgery conducted in Hamad General Hospital, Doha, Qatar was found to be 13.14% which is similar to rates reported in hospitals elsewhere in the world; although elective surgery is performed six days a week from 7:00 am to 10:00 pm in our hospital. Simple and systematic analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 33 publications
2
14
0
8
Order By: Relevance
“…Orthopedia has been pointed out by other studies as having cancellation percentages close to the ones found in this study, such as: 17.85% (27) and 18.4% (7) . Studies have indicated seasonality of surgical cancellations, such as winter months having higher rates of surgery cancellations.…”
Section: Discussionsupporting
confidence: 87%
“…Orthopedia has been pointed out by other studies as having cancellation percentages close to the ones found in this study, such as: 17.85% (27) and 18.4% (7) . Studies have indicated seasonality of surgical cancellations, such as winter months having higher rates of surgery cancellations.…”
Section: Discussionsupporting
confidence: 87%
“…A patient's absence has been reported to be the reason for 16.8%-23% of cancellations (Gonzalez-Arevalo et al, 2009;Mesmar, Shatnawi, Faori, & Khader, 2011;Sahraoui & Elarref, 2014 According to previous studies, a multiprofessionally modified preoperative pathway did not affect cancellations (Siragusa et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
“…A patient's absence has been reported to be the reason for 16.8%–23% of cancellations (Gonzalez‐Arevalo et al., ; Mesmar, Shatnawi, Faori, & Khader, ; Sahraoui & Elarref, ). The presented preoperative protocol is very patient centred, as all operative patients were contacted and carefully preoperatively prepared for the total operative pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The rates and causes of cancellations are diverse and differ from one hospital to another. 3 Between 10% and 40% of booked elective operations may be cancelled before surgery takes place. 1,2,3,4,5 The most common cause of cancellations was lack of theatre time (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,4,6,7 The other reasons include cancellation due to patient factors, cancellation for poorly optimized medical conditions, or cancellations due to administrative reasons. 2,3,4,6,8 An operating list may over-run because of delayed starts, slow turnover, unanticipated surgical/ anaesthetic problems or staff shortages. 9 Many of these are difficult to quantify.…”
Section: Introductionmentioning
confidence: 99%